Three-Dimensional Model Analysis and Processing - Yu, Faxin; Luo, Hao.; Lu, Zheming; Wang, Pinghui; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Three-Dimensional Model Analysis and Processing" focuses on five hot research directions in 3D model analysis and processing in computer science, i.e., on compression, feature extraction, content-based retrieval, irreversible watermarking and reversible watermarking. The book is based on a wide range of new content, systematic and theoretical, and fully reflects the state-of-the-art in 3D model analysis and processing technologies. This book is intended for researchers, engineers and graduate students working in 3D model analysis and processing. Faxin Yu is an Associate Professor at the School of Aeronautics and Astronautics, Zhejiang University, China; both Zheming Lu and Pinghui Wang are also Professors there; Hao Luo is a Lecturer there.
3D Mesh Compression -- 3D Model Feature Extraction -- Content-Based 3D Model Retrieval -- 3D Model Watermarking -- Reversible Data Hiding in 3D Models.
Keywords: Computer science; Coding theory; Information storage and retrieval systems; Computer graphics; Computer vision; Visualization; Computer Science; Computer Graphics; Information Storage and Retrieval; Mathematical Modeling and Industrial Mathematics; Coding and Information Theory; Visualization; Image Processing and Computer Vision